Dibenzocyclooctadiene lignans from the roots of Kadsura coccinea (Lem.) A. C. Smith. - Kiệm, Phan Văn; Thanh, Bùi Văn; Bản, Ninh Khắc; Hương, Hoàng Thanh; Cường, Nguyễn Xuân; Nam, Nguyễn Hoài; Minh, Châu Văn (Vietnam Journal of Chemistry, 2012)
Phytochemical investigation of the methanolic extract of the roots of Kadsura coccinea (Lem.) A. C. Smith led to the isolation of two dibenzocyclooctadiene lignans Binankadsurin A (1) and Kadsuralignan J (2). Their structures were identified by spectroscopic methods including ESI-MS, 1D- and 2D-NMR in comparison with the literature.